Two new records of the tribe Cardiastethini (Hemiptera: Heteroptera: Anthocoridae) from the Korean Peninsula - Jung, Sunghoon; Lee, Seunghwan (Zootaxa, 2011)
The tribe Cardiastethini Carayon 1972 belongs in the family Anthocoridae (Heteroptera: Cimicomorpha). As with other anthocorid flower bugs, the members of the Cardiastethini prey on small arthropods. The predaceous habits of many anthocorids have attracted the attention of researchers who work in agro-ecosystems (e.g., biological control; Lattin 1999).